SOFT GROUND IMPROVEMENT BELOW BRIDGE APPROACH FOUNDATION USING CEMENT DEEP MIXING COLUMNS COMBINED WITH GEOTEXTILE - Nguyen Anh, Tuan; Nguyen Ngoc, Thang (Journal of Applied Engineering Science, 2023)
Vehicle load is a dynamic load and embankment load is a static load. These two load types can act simultaneously to accelerate the consolidation rate of the ground under the embankment, which then leads to differential settlement. This differential settlement is dangerous as it can cause sudden bouncing and shock for vehicles on the road. There are also other problems such as the reduction in the exploitation capacity of the construction work due to the reduction in the speed of vehicles going through the positions of settlement. Lower speed increases the waste of means of transport. Excessive settlement can occur from reasons such as improper design or improper construction. This paper uses the finite element method to simulate the construction process of the bridge approach to calculate, and check the stability and deformation of the soft ground under this road. The analysis results show that the settlement of the ground without treatment is quite large at 1.06 m. After reinforcement, the settlement is 0.013 m, and the stability coefficient increases from 1.032 to 2.739. The research results can be applied to reinforce the bridge approach with a system of cement deep mixing (CDM) columns combined with geotextiles to shorten the construction time and limit settlement compensation.
Keywords: bridge approaches, road embankment, differential settlement, soft soil, CDM